Calcium in Kenyon Cell Somata as a Substrate for an Olfactory Sensory Memory in Drosophila - Lüdke, Alja; Raiser, Georg; Nehrkorn, Johannes; Herz, Andreas V. M.; Galizia, C. Giovanni; Szyszka, Paul (Frontiers in Cellular Neuroscience, 2018)
Animals can form associations between temporally separated stimuli. To do so, the nervous system has to retain a neural representation of the first stimulus until the second stimulus appears. The neural substrate of such sensory stimulus memories is unknown. Here we search for a sensory odor memory in the insect olfactory system and characterize odorant-evoked Ca2+ activity at 3 consecutive layers of the olfactory system in Drosophila: in olfactory receptor neurons (ORNs) and projection neurons (PNs) in the antennal lobe, and in Kenyon cells (KCs) in the mushroom body. We show that the post-stimulus responses in ORN axons, PN dendrites, PN somata and KC dendrites are odor-specific, but they are not predictive of the chemical identity of past olfactory stimuli. However, the post-stimulus responses in KC somata carry information about the identity of previous olfactory stimuli. These findings show that the Ca2+ dynamics in KC somata could encode a sensory memory of odorant identity and thus might serve as a basis for associations between temporally separated stimuli.